Pengaruh Media Sosial Terhadap Persepsi Hukum Islam di Kalangan Generasi Muda Studi Analisis Psikologis - Tsalitsah, imtihanatul; Nur Tualeka, M. Wahid (Muhammadiyah University of Surabaya, 2025)
Abstract: Social media has become an integral part of the daily lives of young people in Indonesia. With easy access to information, social media plays a significant role in shaping their perceptions of Islamic law. This study aims to analyze the influence of social media on perceptions of Islamic law and how psychological factors contribute to this process. Using a mixed-methods approach, data were collected through surveys and in-depth interviews with respondents from diverse backgrounds. The findings indicate that social media not only affects young people's understanding of Islamic law but also shapes their attitudes and behaviors toward its implementation. This study is expected to provide insights for policymakers and educators in designing more effective and relevant educational programs in line with the current digital dynamics. Keywords: social media, Islamic law, psychology